Surface treatment method for improving wear resistance of metal matrix under poor oil lubrication
By designing the composite texture on the surface of the metal matrix and filling it with a responsive multi-composite solid lubricant, the problem of low wear resistance of the metal matrix under oil-free lubrication is solved, and excellent load-bearing performance and self-lubricating performance are achieved, which significantly reduces the friction coefficient and wear rate.
Patent Information
- Application Number
- CN202510050409.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing metal matrix has low wear resistance under oil-free lubrication, resulting in high friction coefficient and high wear rate, which affects the reliability and energy consumption of the equipment.
The surface treatment method is adopted for composite texture and responsive multivariate composite solid lubricant. The composite texture consists of honeycomb-like hexagonal units filled with responsive multivariate composite solid lubricant composed of tin, carbon nanotubes, multivariate two-dimensional materials and NiTi alloy powder.
It significantly reduces the friction coefficient and wear rate of the metal matrix under oil-free lubrication, improves the load-bearing performance and self-lubricating performance, and extends the service life of the equipment.
Smart Images

Figure HDA0005239793170000011 
Figure HDA0005239793170000012 
Figure HDA0005239793170000013
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material surface treatment, and in particular to a surface preparation method for improving the wear resistance of a metal matrix under oil-starved lubrication. Background Art
[0002] With the rapid development of high-end equipment in the fields of aerospace, transportation and energy, the working environment of its friction pairs has become more demanding, requiring breakthroughs in many technical bottlenecks such as environmental adaptability and performance stability. In actual service, the metal contact interfaces of high-end equipment such as bearings and gear pairs often face the problem of ineffective lubrication due to insufficient lubrication, indirect friction and special working conditions, that is, "lack of oil lubrication", which has an important impact on energy consumption, material consumption and equipment reliability. In order to improve the service performance of high-end equipment, it is of great significance to improve the wear resistance of metal substrates under lack of oil lubrication. Generally, surface treatment technologies for improving the wear resistance of metal substrates under lack of oil lubrication can be roughly divided into surface strengthening, surface modification and lubrication system design. In recent years, the use of composite technologies to provide wear resistance of metal substrates under lack of oil lubrication has attracted attention, such as micro-arc oxidation and coating, thermal oxidation and laser surface texturing, surface texturing and solid lubricants.
[0003] At present, there is a composite technology for surface texture and solid lubricant, and solid lubricants are mainly soft metals. This composite technology improves the tribological properties of metal matrix under general lubrication conditions to a certain extent, but there is still a phenomenon of serious lubricant loss in the texture filling area and ineffective lubrication in local areas, resulting in pits on the contact surface. Especially under oil-starved lubrication, the contact interface faces a temperature rise process and significant impact loads in local areas during the transition from oil lubrication to oil-starved lubrication, which seriously affects the adsorption, lubrication and load-bearing properties of the lubricant and the metal matrix. Therefore, how to reduce the tribological properties of metal-based surfaces under oil-starved lubrication through surface texture composite responsive lubricants is of particular importance. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication in response to the deficiencies in the above-mentioned prior art, so that the metal substrate has excellent load-bearing performance and self-lubricating performance under oil-starved lubrication, and can solve the problem of low wear resistance of the existing metal substrate under oil-starved lubrication.
[0005] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0006] A surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication comprises processing a composite texture on the surface of the metal substrate, wherein the composite texture consists of a plurality of hexagonal units arranged in a honeycomb shape, grooves are provided between any adjacent hexagonal units, and a circular groove is provided in the middle of each hexagonal unit; and a responsive multi-component composite solid lubricant is filled in the grooves and circular grooves between any adjacent hexagonal units; wherein the responsive multi-component composite solid lubricant is a composite of tin, carbon nanotubes, multi-component two-dimensional materials and NiTi alloy powder.
[0007] According to the above scheme, the surface area of the responsive multi-composite solid lubricant filling area accounts for 20%-40% of the total surface area of the substrate, the diameter of the circumscribed circle of each hexagonal unit is 1000-2000μm, the groove width is 200-300μm, and the radius of the circular groove is 50-400μm; the depth of the groove and the circular groove is consistent, and the depth range is 30-60μm.
[0008] According to the above scheme, the raw materials in the responsive composite multi-component solid lubricant include, by mass percentage: 70-80wt.% tin powder, 10-15wt.% carbon nanotubes, 6-12wt.% multi-component two-dimensional materials and 3-5wt.% NiTi alloy powder.
[0009] According to the above scheme, the particle size of tin powder in the composite solid lubricant is 50-65μm, with a purity of more than 99%; the diameter of carbon nanotubes is 10-50nm, with a purity of more than 95%; the particle size of NiTi alloy powder is 15-53μm, with a purity of more than 95%.
[0010] According to the above scheme, the multi-element two-dimensional material is prepared by high-temperature reaction synthesis in an argon-enhanced atmosphere containing butyl titanate after coating a mixture of ammonium tungstate, molybdenum, titanium, boron and carbon with molybdenum wire as a carrier. The mixture includes by mass percentage: ammonium tungstate 15-25wt.%, molybdenum 15-25wt.%, titanium 10-18wt.%, boron 8-15wt.% and carbon 30-38wt.%. Furthermore, the preparation method of the multi-element two-dimensional material comprises the following specific steps:
[0011] 1) Mixing: Mixing raw material powders according to mass percentage, wherein the raw materials are 15-25wt.% of ammonium tungstate, 15-25wt.% of molybdenum, 10-18wt.% of titanium, 8-15wt.% of boron and 30-38wt.% of carbon, and mixing by a vibration mixer to obtain a mixed material;
[0012] 2) Sintering: Add water to the mixture to make a viscous paste, evenly apply it on the molybdenum wire, and use a molybdenum wire furnace for sintering. Use argon atmosphere, the argon flow rate is 60-100mL / min, and the argon flow passes through titanate butyrate into the molybdenum wire furnace. The sintering temperature is 800-1000°C and the insulation time is 60-80min. After the insulation is completed, a multi-dimensional two-dimensional material is formed on the surface of the molybdenum wire, which is scraped off for later use.
[0013] Furthermore, the surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication mainly comprises the following steps:
[0014] (1) grinding and polishing the surface of the metal substrate to a surface roughness of less than 0.02 μm, and then cleaning and drying;
[0015] (2) Using a laser marking machine to process a preset composite texture on the surface of the metal substrate, then immersing it in a zinc chloride solution to remove the oxide layer (zinc chloride can dissolve metal oxides), washing it and then drying it; this step facilitates improving the bonding between the responsive multi-component composite solid lubricant and the metal substrate;
[0016] (3) The responsive multi-component composite solid lubricant is filled into the grooves and circular grooves of the composite texture by vacuum infiltration technology, and then polished again to a surface roughness of about 0.01 μm to obtain a metal matrix suitable for oil-starved lubrication.
[0017] In the present invention, the metal substrate is mainly alloy structural steel, such as 20CrMnTi, 40Cr and 42CrMo. The present invention takes 42CrMo alloy steel as an example, but is not limited to this substrate. Before processing the composite texture on the surface of the metal substrate, it is first polished and cleaned until its surface roughness is less than 0.02μm, cleaned and dried.
[0018] In the present invention, oil-starved lubrication specifically includes the situation that when the mechanical moving parts are started / stopped, the lubricating oil causes the upper surface of the mechanical parts to be in dry friction or intermittent lubrication under the action of gravity, and there is no lubricating oil for a short time.
[0019] According to the above scheme, the vacuum infiltration method is as follows: the responsive multi-component composite solid lubricant and the metal matrix are placed on a crucible and a fixed support in a vacuum pressure infiltration furnace, respectively, and the vacuum is evacuated to 0.1-0.2×10 -2 Pa, heating temperature is 600-800℃, after keeping warm for 120-150min, the solid lubricant is melt-infiltrated into the grooves and circular grooves of the composite texture of the metal matrix, and the gas pressure is raised to 1.5-2.0MPa, the infiltration time is 60-90min; then the furnace is cooled to room temperature.
[0020] According to the above scheme, processing composite texture on the surface of metal substrate can be achieved by using laser marking machine, the power of laser marking is: 18-27W, the number of scans is: 20-60 times, and the scanning speed of laser is: 1600-3000mm / s.
[0021] The present invention controls the load-bearing performance of the metal matrix by designing the shape and geometric parameters of the surface texture, and improves the lubrication performance of the metal matrix composite material by modifying the solid lubricant, thereby effectively solving the problem of effectively unifying the load-bearing capacity and lubrication capacity of the metal matrix surface. The technical concept of the present invention is as follows:
[0022] The essential reason why the tribological performance of the metal contact interface is poor under oil-starved lubrication is insufficient oil lubrication or the lubricant cannot function effectively. The composite surface prepared by the surface texture melt-infiltration responsive multi-component composite solid lubricant of the present invention can reduce the friction and wear of the metal substrate surface through solid lubrication when the lubricant cannot function. However, if the texture density of the metal substrate surface is too large, the bearing capacity of the contact interface will be reduced; if the texture density is too small, the filled responsive multi-component composite solid lubricant cannot effectively exert its lubrication performance.
[0023] The present invention utilizes composite texture and responsive multi-component composite solid lubricant under oil-starved lubrication working conditions, and the surface texture adopts a composite texture form of hexagonal grooves nested in circular grooves, and the texture density is within the range of 20-40%.
[0024] The responsive multi-component composite solid lubricant filled in the surface texture of the present invention is the key to solid lubrication under oil-starved lubrication. The responsive multi-component composite solid lubricant is composed of a basic phase, a reinforcing phase and a responsive phase; wherein tin is the basic phase of the solid lubricant; carbon nanotubes and multi-component two-dimensional materials are reinforcing phases, which can improve the adsorption and lubricity of the basic phase and the contact interface. Moreover, carbon nanotubes are 2D additives, which can effectively reduce the friction coefficient; multi-component two-dimensional materials can not only improve the lubrication performance of solid lubricants, but also improve the adsorption of solid lubricants to the surface of the matrix, and reduce the shedding of solid lubricants and the matrix. In addition, NiTi alloy is a responsive phase, and the contact interface faces a temperature rise process during the transition from oil lubrication to oil-starved lubrication. As an intelligent lubricating material, NiTi alloy can actively respond to expansion when the temperature transition point is reached, so that the solid lubricant spreads on the contact interface to form a lubricating film, thereby reducing the wear of the metal matrix.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The metal substrate obtained by the surface treatment method of the present invention has excellent friction reduction and wear resistance, and the friction coefficient and wear rate under oil-starved lubrication are significantly reduced, which can solve the problems of high friction coefficient and high wear rate of the metal substrate surface under oil-starved lubrication.
[0027] 2. The surface of the metal matrix obtained by the treatment method of the present invention has a composite texture and a responsive multi-component composite solid lubricant. When the temperature of the contact interface rises significantly, the NiTi alloy will gradually expand automatically when the temperature reaches the response point, prompting the solid lubricant to spread on the contact interface. In addition, the mutual extrusion of the interface will also prompt the solid lubricant to spread to the contact interface to form a transfer film, thereby avoiding direct contact between the friction pairs to play a wear-resistant role. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a morphology diagram of the multi-element two-dimensional material in Example 1;
[0029] Figure 2 is a morphology diagram of the carbon nanotubes in Example 3;
[0030] Figure 3 1 is a topographical image of the composite texture prepared in Example 2 (wherein the black area is the filling area of the responsive multi-component composite solid lubricant) and the surface of the metal substrate finally obtained;
[0031] Figure 4 is the average friction coefficient of the samples prepared in Example 1, Example 2 and Example 3 under oil-starved lubrication;
[0032] Figure 5 The instantaneous friction coefficient of 42CrMo alloy steel and the 42CrMo alloy steel substrate obtained by the surface treatment method of Example 3 under oil-starved lubrication. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.
[0034] In the following examples, the particle size of the tin powder is in the range of 50-65 μm, and the purity is above 99%; the diameter of the carbon nanotube is in the range of 10-50 nm, and the purity is above 95%; the particle size of the NiTi alloy powder is in the range of 15-53 μm, and the purity is above 95%.
[0035] Example 1
[0036] A surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication, the specific steps are as follows:
[0037] Step 1: Grind and polish the surface of 42CrMo alloy steel to make its surface roughness less than 0.02 μm, then clean it with ultrasonic wave in anhydrous ethanol for 5 minutes, and dry it after cleaning for step 2.
[0038] Step 2: Use a 30W laser marking machine to mark the surface of 42CrMo alloy steel according to the parameters of the composite texture, the power is 18W, the number of scans is 60 times, and the scanning speed of the laser is 2800mm / s; the composite texture is composed of a plurality of regular hexagonal units arranged in a honeycomb shape, and grooves are provided between any adjacent regular hexagonal units, and a circular groove is provided in the middle of each regular hexagonal unit; and the responsive multi-composite solid lubricant is filled with the grooves and circular grooves between any adjacent regular hexagonal units; the total area of the grooves and circular grooves accounts for 20% of the total area of the substrate surface, the diameter of the circumscribed circle of each hexagonal unit is 1600μm, the groove width is 250μm, and the radius of the circular groove is 50μm, the distance between the centers of two adjacent circular grooves is 1545μm, and the depth of the hexagonal grooves and the circular grooves is consistent, and the depth range is 50μm;
[0039] Step 3: After soaking the 42CrMo alloy steel obtained in step 2 in a zinc chloride solution for 3 minutes, the surface of the substrate is rinsed with deionized water and then dried to remove the oxide layer and impurities on the surface.
[0040] Step 4: Place the responsive multi-component composite solid lubricant and the metal matrix obtained in step 3 on a crucible and a fixed support in a vacuum pressure infiltration furnace, respectively, and evacuate to 0.12×10 -2 Pa, heating temperature is 650℃, after keeping warm for 140min, the responsive multi-composite solid lubricant is melt-infiltrated into the grooves and circular grooves of the composite texture of the metal matrix (although the non-groove and circular groove areas will also melt-infiltrate a small amount of responsive multi-composite solid lubricant to a certain extent during the operation, the last step of the method will polish until the non-filled area exposes the 42CrMo alloy steel itself), and the gas pressure is raised to 1.6MPa, and the infiltration time is 85min. Cool to room temperature with the furnace, and then polish the metal matrix to a surface roughness of 0.01μm, and obtain a metal matrix suitable for oil-starved lubrication.
[0041] In this embodiment, the responsive multi-component composite solid lubricant is mixed by weight percentage with 75wt.% tin powder, 12wt.% carbon nanotubes, 10wt.% multi-component two-dimensional material and 3wt.% NiTi alloy powder. The preparation method of the multi-component two-dimensional material is as follows: 24wt.% ammonium tungstate, 20wt.% molybdenum, 16wt.% titanium, 10wt.% boron and 30wt.% carbon are mixed by a vibration mixer by weight percentage, deionized water is added to form a viscous paste, and the paste is evenly coated on the molybdenum wire, and then transferred to a molybdenum wire furnace, and 70mL / min of argon is first introduced (argon enters the molybdenum wire furnace through a volumetric flask containing butyl titanate); then the molybdenum wire furnace is used for sintering, the sintering temperature is 950°C, and the holding time is 65min, to obtain a multi-component two-dimensional material, such as Figure 1 The multi-element two-dimensional material has a layered structure, which is conducive to interlayer slippage, thereby reducing friction.
[0042] In order to simulate the lack of oil lubrication conditions, the metal substrate suitable for lack of oil lubrication prepared by the surface treatment method of Example 1 was cut into several test blocks, placed in the lubricating oil and soaked for 30 minutes, and then the test blocks were taken out and left to stand for 30 minutes. No lubricating oil was added during the test. 42CrMo alloy steel without surface treatment was used as a control sample.
[0043] The above test block was subjected to the oil-starved lubrication test at 20N and 1Hz sliding speed. Each friction cycle was 1800s, and the average value was obtained by repeating the test three times. In the oil-starved friction test between the grinding ball and the metal substrate surface of GCr15, the wear rate of the surface of the test block of Example 1 was 2.1×10 -8 cm 3 / (N·m), the average sliding friction coefficient is 0.13, which has good anti-friction and wear resistance. The friction coefficient of the test block surface of the control sample under oil-starved lubrication is 0.18, and the wear rate is 3.8×10 -7 cm 3 / (N·m), there are obvious scratches on the surface.
[0044] Example 2
[0045] A surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication, the specific steps are as follows:
[0046] Step 1: Grind and polish the surface of 42CrMo alloy steel to make its surface roughness less than 0.02 μm, then clean it in anhydrous ethanol with ultrasonic for 8 minutes, and dry it after cleaning for step 2.
[0047] Step 2: Use a 30W laser marking machine to mark the surface of 42CrMo alloy steel according to the parameters of the composite texture, the power is 24W, the number of scans is 40 times, and the scanning speed of the laser is 2000mm / s; the composite texture is composed of a plurality of regular hexagonal units arranged in a honeycomb shape, and grooves are provided between any adjacent regular hexagonal units, and a circular groove is provided in the middle of each regular hexagonal unit; and the responsive multi-composite solid lubricant is filled with the grooves and circular grooves between any adjacent regular hexagonal units; the total area of the grooves and circular grooves accounts for 30% of the total area of the substrate surface, the diameter of the circumscribed circle of each hexagonal unit is 1600μm, the groove width is 250μm, and the radius of the circular groove is 261μm, and the distance between the centers of two adjacent circular grooves is 1545μm; the depths of the hexagonal grooves and the circular grooves are consistent, and the depth range is 50μm;
[0048] Step 3: After soaking the 42CrMo alloy steel obtained in step 2 in a zinc chloride solution for 4 minutes, the surface of the substrate is rinsed with deionized water and then dried to remove the oxide layer and impurities on the surface and improve the bonding between the lubricant and the metal substrate.
[0049] Step 4: Place the responsive multi-component composite solid lubricant and the metal matrix obtained in step 3 on a crucible and a fixed support in a vacuum pressure infiltration furnace, respectively, and evacuate to 0.16×10 -2 Pa, heating temperature is 700℃, after keeping warm for 130min, the responsive multi-component composite solid lubricant is melt-infiltrated into the grooves and circular grooves of the composite texture of the metal matrix, and the gas pressure is raised to 1.8MPa, and the infiltration time is 70min. Cool to room temperature with the furnace, and then polish the surface roughness of the metal matrix to 0.01μm, and obtain a metal matrix suitable for oil-starved lubrication.
[0050] In this embodiment, the responsive multi-component composite solid lubricant is mixed by weight percentage with 74wt.% of tin powder, 10wt.% of carbon nanotubes, 12wt.% of multi-component two-dimensional material and 4wt.% of NiTi alloy powder. The preparation method of the multi-component two-dimensional material is as follows: 18wt.% of ammonium tungstate, 23wt.% of molybdenum, 18wt.% of titanium, 8wt.% of boron and 33wt.% of carbon are mixed by a vibration mixer by weight percentage, deionized water is added to make a viscous paste material, which is evenly coated on the molybdenum wire, and then transferred to a molybdenum wire furnace, and 80mL / min of argon is first introduced (argon enters the molybdenum wire furnace through a volumetric bottle containing butyl titanate); then the molybdenum wire furnace is used for sintering, the sintering temperature is 900°C, and the holding time is 90min to obtain the multi-component two-dimensional material.
[0051] In order to simulate the lack of oil lubrication conditions, the metal substrate suitable for lack of oil lubrication prepared by the surface treatment method of Example 2 was cut into several test blocks, placed in the lubricating oil and soaked for 30 minutes, and then the test blocks were taken out and left to stand for 20 minutes. No lubricating oil was added during the test. The 42CrMo alloy steel without surface treatment was used as a control sample.
[0052] The above test block was subjected to the oil-starved lubrication test at 20N and 1Hz sliding speed. Each friction cycle was 1800s, and the average value was obtained by repeating the test three times. In the oil-starved friction test between the grinding ball and the metal substrate surface of GCr15, the wear rate of the surface of the test block of Example 2 was 3.2×10 -8 cm 3 / (N·m), the average sliding friction coefficient is 0.15, which has good anti-friction and wear resistance. The friction coefficient of the control block surface under oil-starved lubrication is 0.22, and the wear rate is 4.4×10 -7 cm 3 / (N·m), there are obvious scratches on the surface.
[0053] Example 3
[0054] A surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication, the specific steps are as follows:
[0055] Step 1: Grind and polish the surface of 42CrMo alloy steel to make its surface roughness less than 0.02 μm, then clean it with ultrasonic wave in anhydrous ethanol for 10 minutes, and dry it after cleaning for step 2.
[0056] Step 2: Use a 30W laser marking machine to mark the surface of 42CrMo alloy steel according to the parameters of the composite texture, the power is 27W, the number of scans is 25 times, and the scanning speed of the laser is 1800mm / s; the composite texture is composed of a plurality of regular hexagonal units arranged in a honeycomb shape, and grooves are provided between any adjacent regular hexagonal units, and a circular groove is provided in the middle of each regular hexagonal unit; and the responsive multi-composite solid lubricant is filled in the grooves and circular grooves between any adjacent regular hexagonal units; the total area of the grooves and circular grooves accounts for 40% of the total area of the substrate surface, the diameter of the circumscribed circle of each hexagonal unit is 1600μm, the groove width is 250μm, and the radius of the circular groove is 366μm, and the distance between the centers of two adjacent circular grooves is 1545μm; the depths of the hexagonal grooves and the circular grooves are consistent, and the depth range is 50μm;
[0057] Step 3: Soak the 42CrMo alloy steel obtained in step 2 in a zinc chloride solution for 5 minutes, rinse the surface of the substrate with deionized water, and then dry it.
[0058] Step 4: Place the responsive multi-component composite solid lubricant and the metal matrix obtained in step 3 on a crucible and a fixed support in a vacuum pressure infiltration furnace, respectively, and evacuate to 0.18×10 -2 Pa, heating temperature is 750℃, after keeping warm for 110min, the responsive multi-component composite solid lubricant is melt-infiltrated into the grooves and circular grooves of the composite texture of the metal matrix, and the gas pressure is raised to 2.0MPa, and the infiltration time is 65min. Cool to room temperature with the furnace, and then polish the surface roughness of the metal matrix to 0.01μm, and obtain a metal matrix suitable for oil-starved lubrication.
[0059] In this embodiment, the responsive multi-component composite solid lubricant is mixed by weight percentage of tin powder 73wt.%, carbon nanotubes 14wt.%, multi-component two-dimensional material 8wt.% and NiTi alloy powder 5wt.%. The preparation method of the multi-component two-dimensional material is as follows: 20wt.% of ammonium tungstate, 18wt.% of molybdenum, 15wt.% of titanium, 12wt.% of boron and 35wt.% of carbon are mixed by a vibration mixer by weight percentage, deionized water is added to make a viscous paste material, which is evenly coated on the molybdenum wire, and then transferred to a molybdenum wire furnace, and 100mL / min of argon is first introduced (argon enters the molybdenum wire furnace through a volumetric bottle containing butyl titanate); then the molybdenum wire furnace is used for sintering, the sintering temperature is 850°C, and the holding time is 80min to obtain the multi-component two-dimensional material.
[0060] In order to simulate the starved oil lubrication condition, the metal substrate suitable for starved oil lubrication prepared by the surface treatment method of Example 3 was cut into several test blocks, placed in the lubricating oil and soaked for 30 minutes, and then the test blocks were taken out and left to stand for 10 minutes. No lubricating oil was added during the test. The 42CrMo alloy steel without surface treatment was used as a control sample.
[0061] The above test block was subjected to the oil-starved lubrication test at 20N and 1Hz sliding speed. Each friction cycle was 1800s, and the average value was obtained by repeating the test three times. In the oil-starved friction test between the grinding ball and the metal substrate surface of GCr15, the wear rate of the surface of the test block of Example 3 was 1.4×10 -8 cm 3 / (N·m), the average sliding friction coefficient is 0.10, which has good anti-friction and wear resistance. The friction coefficient of the test block surface of the control sample under oil-starved lubrication is 0.12, and the wear rate is 2.7×10 -7 cm 3 / (N·m), there are obvious scratches on the surface.
[0062] Obviously, the wear resistance of the metal substrate prepared by the surface treatment method of the present invention is significantly improved in the lack of oil lubrication performance. In the lack of oil friction test between the spherical surface and the plane, the load is 20N, the reciprocating friction is 30min, and the wear rate of the metal substrate surface is 1.2-3.5×10 -8 cm 3 / (N·m), sliding friction coefficient: 0.09-0.178, with good friction reduction and wear resistance. Therefore, the metal substrate surface suitable for oil-starved lubrication prepared by the surface treatment method of the present invention has excellent wear resistance, and the friction coefficient and wear rate are significantly lower, and the wear resistance under oil-starved lubrication is significantly better than that of ordinary alloy steel surface.
[0063] The above are only examples of the features of the present invention and do not constitute any limitation on the protection scope of the present invention. Any technical solution formed by equivalent exchange or equivalent replacement falls within the protection scope of the present invention.
Claims
1. A surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication, characterized in that: A composite texture is processed on the surface of a metal substrate, wherein the composite texture consists of a plurality of hexagonal units arranged in a honeycomb shape, grooves are provided between any adjacent hexagonal units, and a circular groove is provided in the middle of each hexagonal unit; and a responsive multi-component composite solid lubricant is filled in the grooves and circular grooves between any adjacent hexagonal units; wherein the responsive multi-component composite solid lubricant is a composite of tin, carbon nanotubes, multi-component two-dimensional materials and NiTi alloy.
2. A surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication according to claim 1, characterized in that: The surface area of the responsive multi-component composite solid lubricant filling region accounts for 20%-40% of the total surface area of the substrate, and the depths of the grooves and circular grooves are both 30-80 microns.
3. The surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication according to claim 1, characterized in that: The diameter of the circumscribed circle of each hexagonal unit is 1000-2000 microns, the groove spacing is 200-300 microns, and the radius of the circular groove is 50-400 microns.
4. The surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication according to claim 1, characterized in that: The raw materials in the responsive composite multi-component solid lubricant include, by mass percentage, 70-80wt.% tin powder, 10-15wt.% carbon nanotubes, 6-12wt.% multi-component two-dimensional materials and 3-5wt.% NiTi alloy powder.
5. The surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication according to claim 1, characterized in that: The multi-element two-dimensional material is prepared by high-temperature reaction synthesis in an argon-enhanced atmosphere containing butyl titanate after being coated with a mixture of ammonium tungstate, molybdenum, titanium, boron and carbon using molybdenum wire as a carrier; wherein the mixture includes, by mass percentage, 15-25wt.% of ammonium tungstate, 15-25wt.% of molybdenum, 10-18wt.% of titanium, 8-15wt.% of boron and 30-38wt.% of carbon.
6. A surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication according to claim 5, characterized in that: The preparation method of the multi-element two-dimensional material comprises the following specific steps: 1) Mixing: Mixing raw material powders according to mass percentage, wherein the raw materials are 15-25wt.% of ammonium tungstate, 15-25wt.% of molybdenum, 10-18wt.% of titanium, 8-15wt.% of boron and 30-38wt.% of carbon, and mixing by a vibration mixer to obtain a mixed material; 2) Sintering: Add water to the mixture to make a viscous paste, evenly apply it on the molybdenum wire, and use a molybdenum wire furnace for sintering. Use argon atmosphere, the argon flow rate is 60-100mL / min, and the argon flow passes through titanate butyrate into the molybdenum wire furnace. The sintering temperature is 800-1000°C and the insulation time is 60-80min. After the insulation is completed, a multi-dimensional two-dimensional material is formed on the surface of the molybdenum wire, which is scraped off for later use.
7. A surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication according to any one of claims 1 to 5, characterized in that: The main steps are as follows: (1) grinding and polishing the surface of the metal substrate to a surface roughness of less than 0.02 μm, followed by cleaning and drying; (2) using a laser marking machine to process a preset composite texture on the surface of the metal substrate, then immersing it in a zinc chloride solution, cleaning it, and drying it; (3) The responsive multi-component composite solid lubricant is filled into the grooves of the composite texture by using vacuum infiltration technology, and then polished again to reduce the surface roughness to less than 0.02 μm, thereby obtaining a metal matrix suitable for oil-starved lubrication.
8. A surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication according to claim 7, characterized in that: The metal matrix is alloy structural steel.
9. The surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication according to claim 7, characterized in that: The vacuum infiltration method is as follows: the responsive multi-component composite solid lubricant and the metal matrix are placed on a crucible and a fixed support in a vacuum pressure infiltration furnace, and the vacuum is evacuated to 0.1-0.2×10 -2 Pa, heating temperature is 600-800℃, after keeping warm for 120-150min, the solid lubricant is melt-infiltrated into the grooves and circular grooves of the composite texture of the metal matrix, and the gas pressure is raised to 1.5-2.0MPa, the infiltration time is 60-90min; then the furnace is cooled to room temperature.
10. The surface treatment method for improving the wear resistance of a metal substrate under oil-starved lubrication according to claim 7, characterized in that: The composite texture is processed on the surface of the metal substrate by a laser marking machine. The power of the laser marking is 18-27W, the number of scans is 20-60 times, and the scanning speed of the laser is 1600-3000mm / s.
Citation Information
Patent Citations
Titanium-rich titanium nickel alloy with negative heat expansion performance and preparation method thereof
CN107164653A
Wear-resistant noise-reducing metal-based high-speed rail brake pad and preparation method thereof
CN112377548A
Preparation method of two-dimensional lamellar carbon-based molybdenum carbide composite material
CN112609197A
Surface micro-pit self-lubricating coating and preparation method thereof
CN113445043A
NiTi-based self-lubricating composite material and preparation method thereof
CN113802029A